Wealth Redistribution, Race & Southern Public Schools, 1880-1910 - Kenneth Ng (Arizona State University, 2001)
This article measures the wealth redistribution effected by southern public schools and the taxes which supported them. It extends and contributes to the existing literature on this subject in three ways. First, the measurement is based on a larger sample of southern states and over more years than previous efforts. Second, this article establishes that from 1880 to 1910 throughout the South the public schools were a conduit for a consistent and significant flow of resources from whites to blacks. Blacks did not pay enough taxes to fully finance black public schools even at the lower levels dictated by white controlled school boards. Third, the establishment of segregated schools and the disenfranchisement of southern blacks did not eliminate this transfer but only moderately reduced it. The effect of Plessy v. Ferguson and the establishment of segregated schools was not as large as previously thought.